Peningkatan Kapasitas UMKM Kuliner dalam Layanan Pelanggan Digital melalui Implementasi WhatsApp Business dan Chatbot - Astri R Banjarnahor; Chandra M. Saputra; Datunabolon Datunabolon; Asep Mulyawan; Mutiara Gani (Pusat Riset dan Inovasi Nasional, 2025)
This Community Service activity aims to increase the capacity of MSME actors in the culinary sector in South Tangerang in utilizing digital technology, especially WhatsApp Business and chatbots, as a tool to increase their business competitiveness. Based on data from the Ministry of Trade (2023), there are 92,783 MSMEs in this region, with the dominance of the culinary sector. However, there are still many MSME actors who experience gaps in digital literacy, which hinders their development in this digital era. This training involved 30 participants from various culinary businesses in South Tangerang, and was carried out with an approach consisting of theory, direct practice, and technical assistance. To evaluate the effectiveness of the training, a pre-test and post-test were conducted. The results showed a significant improvement in participants' understanding, with the average score increasing from 42% on the pre-test to 86% on the post-test. In addition, participants also managed to build a simple chatbot flow that can be used to improve their customer service. The level of satisfaction of participants with this training was very high, with 90% of participants stating that they were satisfied or very satisfied with the material and implementation of the training. The results of this activity show that digital technology-based training can effectively improve the operational and communication skills of MSME actors, which in turn can strengthen their competitiveness. Therefore, it is recommended to strengthen advanced training programs as well as technology incubation tailored to the needs of each sector. This will help address the existing digital literacy gap and provide ongoing support for MSMEs. Thus, this training is expected to make a real contribution to improving the digital competence of MSME actors, especially in the culinary sector, and strengthening their position in an increasingly competitive market.